Police Duties and Functions in Realizing Justice and Legal Certainty Under Police Law No. 2 Of 2002 - Yoan Febriawan (Riviera Publishing, 2024)
The National Police of the Republic of Indonesia (Polri) holds a crucial role in upholding security and public order (Kamtibmas) as one of the key state institutions. Governed by Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia, this research aims to scrutinize and assess the duties and functions assigned to the police according to this legislation, with a focus on their ability to achieve justice and legal certainty. Employing normative research methods, this study relies on a literature review as its primary data collection technique. The collected data undergoes analysis through three stages: data reduction, data presentation, and conclusion drawing. The findings of this research reveal that under Police Law No. 2 of 2002, the functions of the police are outlined in Article 2. These functions encompass maintaining security and public order, law enforcement, protection, and community service, positioning the police as an integral part of state governance. Additionally, Article 13 delineates the primary duties of the police, emphasizing their responsibility in maintaining security and public order, enforcing laws, and offering protection, guidance, and service to the community.